Vaccination in Pediatric Patients with Sickle-Cell Disease: Uptake Report and Mini-Review. (10th May 2022) - Jarovsky, Daniel; Bastos, Phillipe Romanzini; de Matos, Samantha Faria; Almeida, Flávia Jacqueline; Sáfadi, Marco Aurélio Palazzi; Hegg, Izabella Campos Oliveira; Luporini, Silvia Maria; Berezin, Eitan Naaman
Abstract: Background: Brazil has one of the highest numbers of births with sickle-cell disease (SCD) in the Americas. Despite the risk of severe illnesses and death due to both vaccine-preventable infections, vaccination uptake in pediatric patients with SCD is unknown. Material and methods: Children under 18 years with SCD presenting to routine medical consultations had their vaccination status evaluated according to the national recommendations. Data obtained were classified as 'Adequate', 'Delayed' or 'Missing' vaccination and compared among age groups. Results: From 117 children screened, 100 had their vaccination card available. Vaccination coverage of routine vaccines was above 95% for all primary series and both age groups, with varied rates of delays and low missing doses. Among SCD extended vaccination, the most frequently delayed and missed vaccines were those specifically recommended to individuals with SCD as per national guidelines—and particularly those against encapsulated bacteria. Significant and varied rates of missing doses occurred in primary series and booster doses for PPSV23, Hib, menC, hepatitis A and varicella. The average influenza vaccination rate was 69.5%, with higher rates among younger children. Conclusions: Children with SCD have alarming under-vaccination rates. Basic prevention strategies in Brazil should be reassessed in this specific population.